THE ROLE OF ACTIVITY CENTERS IN DEVELOPING SOCIAL COMPETENCIES OF OLDER PRESCHOOL CHILDREN - Eshmurodova Ozoda Zafar qizi (International Journal of Literature and Language Studies, 2026)
This article examines the role of activity centers in developing social competencies of older preschool children. Social competence is one of the key indicators of a child’s readiness for school and successful participation in social life. In preschool education, activity centers create favorable pedagogical conditions for communication, cooperation, self-expression, problem-solving, emotional regulation, and independent decision-making. The article analyzes the educational importance of play, construction, art, language, science, and role-play centers in forming children’s social behavior. It also discusses how activity centers support peer interaction, responsibility, empathy, initiative, and respect for social rules. The study concludes that the effective organization of activity centers in preschool institutions contributes significantly to the holistic development of older preschool children and prepares them for further learning and social adaptation.